Paul Rusch in Postwar Japan : Evangelism, Rural Development, and the Battle against Communism - McDonald, Andrew T.; McDonald, Verlaine Stoner (Book collections on Project MUSE., 2018)
This text describes the remarkable life of Paul Rusch, a Kentuckian who went to Japan after the Great Kanto Earthquake.